2020
DOI: 10.1111/clr.13626
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and comparison of histologic changes and implant survival in extraction sites immediately grafted with two different xenografts: A randomized clinical pilot study

Abstract: Objectives The purpose of this prospective, single‐center randomized pilot study was to histologically evaluate and compare vital bone development in premolar and molar‐extraction sites grafted with two different bovine‐derived xenografts. The secondary outcome of interest was implant survival in the grafted sites. Materials and Methods Adult patients in need of at least two tooth extractions were enrolled. A paired design was used; each patient received at least one of each type of graft at different sites. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…Our histological results are in accordance with the literature: 33.79 ± 17.37% vital bone at the grafted sites and 51.14 ± 23.04% at sites of spontaneous healing. Similar results (~30% vital bone) were reported by other investigators that used DBBM‐C for ridge preservation 7,27 . In other studies which used particulated DBBM grafts for ARP, the amount of newly formed bone varied from 21.5% after 4–6 months 6 to 43% after 9 months 28 .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our histological results are in accordance with the literature: 33.79 ± 17.37% vital bone at the grafted sites and 51.14 ± 23.04% at sites of spontaneous healing. Similar results (~30% vital bone) were reported by other investigators that used DBBM‐C for ridge preservation 7,27 . In other studies which used particulated DBBM grafts for ARP, the amount of newly formed bone varied from 21.5% after 4–6 months 6 to 43% after 9 months 28 .…”
Section: Discussionsupporting
confidence: 85%
“…The usage of bone grafts in fresh sockets for ARP was introduced in the 1980s 4 . With time, different ARP procedures evolved, using different bone substitutes, as allografts, 5 alloplasts, 6 and xenografts 7 and xenografts embedded in collagen 8…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies [ 8 , 9 ] have shown that placement of implants into the previously grafted sockets is comparable to that into the non-grafted sites.…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of DBBM resulted in 46.44% of VB, while the application of FDBA exhibited a 48.54%. A previous research using DBBM have found a 32,4% of VB, after 4 months (Sivolella et al, 2020), while two investigations observed 27.35% (Gholami et al, 2012) and 31.4% (Barone et al, 2013), at 6 months. Similarly, the use of FDBA has also reported inferior results in terms of VB than the ones obtained in the present investigation, showing a 26.40% of new bone formation, after 18–20 weeks (Demetter et al, 2017).…”
Section: Discussionmentioning
confidence: 88%